Entangled states of being - Lee, Monica Wan Wen (Nanyang Technological University, 2024)
Entangled States of Being is rooted in the inquiry of the nature of reality, unravelling the connections and complexities of human experience and the relentless pursuit of meaning. Drawing inspiration from concepts found in quantum physics and Carl Jung’s theory of archetypes, Entangled States of Being metaphorically unravels through a non-linear narrative, revealing an intricate connection between life, perception and reality. At the crux of this project lies the question: do humans possess the agency to shape our reality, or do forces beyond our comprehension predetermine our experiences? As we obtain answers to such existential mysteries, we will reach a fork in the road where we have to choose if these revelations confound us or offer profound tranquillity.